Maximizing blue carbon stocks through saltmarsh restoration - McMahon, Lucy; Ladd, Cai J. T.; Burden, Annette; Garrett, Ed; Redeker, Kelly R.; Lawrence, Peter; Gehrels, Roland (Frontiers in Marine Science, 2023)
Political discourse around coastal wetland restoration and blue carbon management strategies has increased in the past decade, yet carbon storage has neither been a reason for restoration, nor a criterion to measure the success of current saltmarsh restoration schemes in the UK. To maximise climate change mitigation through saltmarsh restoration, knowledge on the key drivers of carbon stock variability is required. We use restored saltmarshes of similar age, paired with adjacent natural marshes as references, to identify drivers of carbon stocks following managed realignment within an estuary in southeastern England. From surficial soil cores (top 30 cm), we measured carbon stock alongside environmental characteristics. Carbon stock between natural and restored sites were similar after ~ 30 years when restored sites were above mean high water neap (MHWN) tidal levels. Elevated marsh platforms likely provide suitable conditions for the development of mature plant communities associated with greater capture and production of organic carbon. The restored site at Tollesbury (Essex, UK) had a 2-fold lower carbon stock than other restored sites in the estuary. We attribute this to the site’s low position in the tidal frame, below MHWN tidal levels, coupled with low sediment supply and the dominance of pioneer plant communities. As blue carbon is anticipated to become an important facet of saltmarsh restoration, we recommend sites above MHWN tidal levels are selected for managed realignment. If only low elevation sites are available, preference should be given to coastlines with a high sediment supply that may rapidly elevate realignment sites. Alternatively, elevation could be artificially raised prior to realignment. Restoration schemes aiming to maximise climate change mitigation should also encourage the establishment of key plant species (e.g., Atriplex portulacoides in our study) to enhance carbon stocks. However, the overall goal of restoration ought to be carefully considered as trade-offs in ecosystem services may ensue if restoration for climate change mitigation alone is pursued.